A catalyst for solar photo-thermal driving carbon dioxide hydrogenation to produce methane, and a preparation method and application thereof
Patent Information
- Application Number
- CN202611197241.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-07
- Publication Date
- 2026-10-16
AI Technical Summary
本发明通过载体形貌调控与活性组分精准负载,开发出一种可充分利用太阳能的光热协同高效催化剂,有效解决了传统催化剂光能利用率低、热稳定性差、CO2转化率及甲烷选择性不足的问题,且催化剂制备工艺简单、条件温和、成本较低,适合规模化生产与工业化应用
[0021] 1. This invention employs a mild and controllable photodeposition loading process to uniformly modify ultra-small Ru nanoclusters onto the surface of a self-prepared nanoflower-like Nb₂O₅ support. This preparation method achieves low Ru loading and high dispersion anchoring; the in-situ generated Ru nanoclusters are uniform in size, well-dispersed, and tightly bonded to the support interface, effectively inhibiting the migration, aggregation, and detachment of active components, significantly improving the structural stability and cycle life of active sites. Simultaneously, the catalyst preparation process of this invention is simple to operate, the process is controllable, requires no toxic additives or complex post-processing steps, is environmentally friendly, has low preparation cost, and high reproducibility, possessing feasibility for large-scale mass production and industrial application value.
Smart Images

Figure CN122912848A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of new energy catalytic materials and carbon dioxide resource utilization technology, and in particular to a catalyst for solar thermal-driven carbon dioxide hydrogenation to methane, its preparation method and application. Background Technology
[0002] With the rapid advancement of global industrialization, the massive consumption of fossil fuels such as coal, oil, and natural gas has led to a continuous rise in atmospheric CO2 concentrations, triggering a series of ecological and environmental problems, including global warming. At the same time, traditional fossil fuel reserves are dwindling, exacerbating the energy supply-demand imbalance. Against this backdrop, CO2 catalytic conversion technology has become a key technological approach for achieving carbon resource recycling, reducing greenhouse gas emissions, and alleviating the energy crisis. This technology can efficiently convert CO2 captured from industrial waste gas and the atmosphere into clean carbon-based fuels such as methane, possessing both ecological and environmental value as well as energy resource utilization value, making it an important research direction for promoting the green energy transition.
[0003] While traditional thermocatalytic CO2 conversion technologies have a high degree of industrialization and can achieve large-scale CO2 conversion, their reaction processes require maintaining high temperatures, resulting in significant energy consumption, which contradicts the current industry trend towards low-carbon, green, and sustainable development. Solar-driven photocatalytic CO2 conversion technology, relying on clean energy to achieve a zero-carbon emission reaction process, possesses inherent advantages in terms of greenness and low carbon emissions. However, single photocatalytic technologies generally suffer from low solar energy utilization and slow reaction kinetics, greatly limiting CO2 catalytic conversion efficiency and making it difficult to meet the needs of large-scale industrial applications.
[0004] Solar photothermal coupled catalysis technology can leverage the dual advantages of light excitation and thermal activation, utilizing solar energy to simultaneously provide the light and heat energy required for the reaction, significantly reducing reaction energy consumption. It also effectively optimizes catalytic reaction kinetics, improving CO2 conversion efficiency and product selectivity, making it a cutting-edge technology direction for CO2 resource utilization. However, existing photothermal catalysts still have many shortcomings and cannot meet practical needs: 1) Poor dispersion of active components, prone to agglomeration and sintering, resulting in poor catalytic stability; 2) Weak light absorption capacity, unable to efficiently capture solar energy and achieve photothermal synergistic catalysis; 3) Insufficient effective active sites on the surface, resulting in weak adsorption and activation capacity for CO2, leading to low CO2 conversion rate and numerous byproducts.
[0005] Therefore, developing catalysts with excellent light absorption and photothermal conversion capabilities, as well as high activity, high selectivity, and high stability, to match the solar photothermal CO2 hydrogenation to methane reaction system, while designing a simple and controllable preparation process, are the technical problems that urgently need to be solved in this field. Summary of the Invention
[0006] The purpose of this invention is to overcome the aforementioned problems in traditional technologies and provide a catalyst for solar-thermal CO2 hydrogenation to methane, its preparation method, and its application. This invention develops a highly efficient photothermal catalyst that fully utilizes solar energy through support morphology control and precise loading of active components. It effectively solves the problems of low light energy utilization, poor thermal stability, and insufficient CO2 conversion and methane selectivity in traditional catalysts. Furthermore, the catalyst preparation process is simple, the conditions are mild, and the cost is low, making it suitable for large-scale production and industrial applications.
[0007] To achieve the above-mentioned technical objectives and effects, the present invention is implemented through the following technical solution:
[0008] This invention discloses a catalyst for solar thermal-driven carbon dioxide hydrogenation to methane production. The catalyst is a ruthenium-based supported catalyst, which is composed of ruthenium (Ru) nanoclusters and niobium pentoxide (Nb2O5) support. The niobium pentoxide support has a flower-like hierarchical structure formed by assembling nanosheets, and the ruthenium nanoclusters are uniformly loaded on the surface of the nanosheets of the niobium pentoxide support.
[0009] Furthermore, the ruthenium nanoclusters have a particle size distribution of 0.9–1.4 nm.
[0010] Furthermore, the method for preparing the catalyst includes the following steps:
[0011] 1) Preparation of niobic acid precursor: Soluble niobium (Nb) raw material is dissolved in a mixture of ethanol and water, stirred evenly, and concentrated ammonia is added dropwise to form a suspension. The solid precipitate is collected by centrifugation. The solid precipitate is dispersed in an aqueous solution of polyvinylpyrrolidone, stirred evenly, and subjected to a hydrothermal reaction. After the reaction is completed, the mixture is cooled, centrifuged, washed, and dried to obtain the niobic acid precursor.
[0012] 2) Carrier preparation: The niobate precursor was ground, calcined in air, cooled, and ground again to obtain a nano-flower-like niobium pentoxide carrier;
[0013] 3) Catalyst preparation: The niobium pentoxide support was dispersed in an aqueous solution containing ruthenium precursor and ultrasonically homogenized. Photodeposition reaction was carried out under an inert protective atmosphere and light irradiation. After the reaction was completed, the catalyst was centrifuged and vacuum dried to obtain the target catalyst.
[0014] Further, in step 1), the hydrothermal reaction temperature is 160–200 °C, the hydrothermal reaction time is 18–24 h, and the mass fraction of the concentrated ammonia solution is 25%–28%.
[0015] Further, in step 1), the mass ratio of Nb element, ethanol, and water is 0.2–1:20:100, the mass ratio of concentrated ammonia to water is 3–5:20, and the mass ratio of polyvinylpyrrolidone to water is 0.5–2:100.
[0016] Furthermore, in step 2), the calcination temperature is 400–600 °C, and the calcination time is 2–4 h.
[0017] Further, in step 3), the mass ratio of niobium pentoxide, Ru, and water is 0.02:0.0001 to 0.0016:20.
[0018] This invention also provides the application of a catalyst in a solar thermal-driven reaction of carbon dioxide hydrogenation to methane.
[0019] Furthermore, the carbon dioxide hydrogenation to methane reaction is a gas-solid photothermal catalytic reaction, and the reaction system is a batch reaction system or a continuous flow reaction system. The reaction process uses solar energy as the only energy source, without the need for additional heating, and the methane selectivity of the reaction product can reach 100%.
[0020] The beneficial effects of this invention are:
[0021] 1. This invention employs a mild and controllable photodeposition loading process to uniformly modify ultra-small Ru nanoclusters onto the surface of a self-prepared nanoflower-like Nb₂O₅ support. This preparation method achieves low Ru loading and high dispersion anchoring; the in-situ generated Ru nanoclusters are uniform in size, well-dispersed, and tightly bonded to the support interface, effectively inhibiting the migration, aggregation, and detachment of active components, significantly improving the structural stability and cycle life of active sites. Simultaneously, the catalyst preparation process of this invention is simple to operate, the process is controllable, requires no toxic additives or complex post-processing steps, is environmentally friendly, has low preparation cost, and high reproducibility, possessing feasibility for large-scale mass production and industrial application value.
[0022] 2. The catalyst of this invention exhibits a nano-flower-like microstructure with a large specific surface area, which facilitates the exposure of abundant active sites, thereby significantly enhancing the adsorption and activation capacity for reactant molecules. The catalyst of this invention possesses excellent light absorption performance and outstanding photothermal conversion capability, enabling efficient capture and utilization of sunlight to achieve highly efficient photothermal synergistic catalytic reduction of CO2.
[0023] 3. When applied to the solar-driven photothermal catalytic CO2 hydrogenation to methane reaction, the catalyst of this invention exhibits excellent catalytic performance, demonstrating not only a high methane yield but also 100% methane product selectivity. Furthermore, this catalyst possesses excellent long-term operational stability, showing no significant attenuation of catalytic activity under continuous reaction conditions and exhibiting a long service life.
[0024] Of course, any product implementing this invention does not necessarily need to achieve all of the above advantages at the same time. Attached Figure Description
[0025] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0026] Figure 1 These are X-ray diffraction (XRD) patterns of the catalysts prepared in Example 1 and Comparative Examples 1-4;
[0027] Figure 2 This is a scanning electron microscope (SEM) image of the catalyst prepared in Example 1;
[0028] Figure 3 The catalyst prepared in Example 1 is shown in the following images: (ab) Transmission Electron Microscopy (TEM) images, (c) High Resolution Transmission Electron Microscopy (HRTEM) images, (dg) High Angle Annular Dark Field Scanning Transmission Electron Microscopy (HAADF-STEM) images, and corresponding elemental mapping diagrams of Ru, Nb, and O.
[0029] Figure 4 The N2 isothermal adsorption-desorption curves (a) and the corresponding pore size distribution diagrams (b) of the catalysts prepared in Example 1 and Comparative Example 1 are shown.
[0030] Figure 5 X-ray photoelectron spectroscopy (XPS) of the catalysts prepared in Example 1 and Comparative Example 1: (a) full spectrum, (b) Nb3 d Spectrum, (c)O 1 s Spectrum, (d)Ru 3 p Spectrum;
[0031] Figure 6 The catalysts prepared in Examples 1-4 and Comparative Example 1 were tested under simulated sunlight (320-1100 nm, 2.5 W·cm⁻¹). -2 The CH4 formation rate and selectivity of the photothermal catalytic CO2 hydrogenation reaction under photothermal conditions;
[0032] Figure 7 The catalysts prepared in Example 1 and Comparative Examples 2-4 were tested under simulated sunlight (320-1100 nm, 2.5 W·cm⁻¹). -2 Surface temperature under irradiation and CH4 generation rate in photothermal catalytic CO2 hydrogenation reaction;
[0033] Figure 8The CH4 generation rate of the photothermal catalytic CO2 hydrogenation reaction under sunlight irradiation was simulated using the catalyst prepared in Example 1 under different CO2 concentrations (CO2 to H2 concentration ratio fixed at 3:1, with the balance gas being N2).
[0034] Figure 9 The catalyst prepared in Example 1 demonstrates its performance in a continuous flow reaction under simulated long-term photothermal catalytic reaction of CO2 hydrogenation (CO2:H2 = 1:3, flow rate: 10 mL·min). -1 Illumination conditions: 320-1100 nm, 2.5 W·cm⁻¹ -2 ). Detailed Implementation
[0035] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0036] This invention discloses a ruthenium-based supported catalyst, which is composed of ruthenium (Ru) nanoclusters and a niobium pentoxide (Nb₂O₅) support. The Nb₂O₅ support is a flower-like hierarchical structure assembled from nanosheets. The Ru nanoclusters have a particle size mainly distributed between 0.9 and 1.4 nm and are uniformly supported on the surface of the flower-like Nb₂O₅ nanosheets. The Ru prepared by this invention... NC The Nb2O5 catalyst possesses a large specific surface area and abundant pore structure, enabling efficient adsorption of CO2. Simultaneously, this catalyst exhibits excellent light absorption and photothermal conversion performance, allowing for efficient solar-driven photothermal catalytic CO2 hydrogenation. Furthermore, the catalytic reaction achieves 100% product selectivity for methane (CH4).
[0037] The design principle of the catalyst of this invention is as follows: The catalyst uses nano-flower-like Nb₂O₅ as a support, with Ru nanoclusters loaded on its surface. The synergistic coupling effect of these two components achieves highly efficient photothermal catalytic performance for the hydrogenation of CO₂ to methane. The Nb₂O₅ support possesses excellent ultraviolet light absorption characteristics, generating a large number of photogenerated electron-hole pairs under sunlight excitation, providing a photocatalytic basis for the reaction. Simultaneously, Nb₂O₅ exhibits good thermal stability and abundant Lewis acid-base active sites. On the one hand, it can stabilize and anchor the Ru nanoclusters on its surface, inhibiting their aggregation and sintering during high-temperature reactions, ensuring the stability of the catalyst structure. On the other hand, it can efficiently adsorb and activate CO₂ reactants, providing favorable conditions for the smooth progress of the reaction. The loaded Ru nanoclusters possess a unique localized surface plasmon resonance (LSPR) effect, which can further broaden and enhance the catalyst's light absorption capacity, while also exhibiting excellent photothermal conversion effects, rapidly increasing the catalyst surface temperature and effectively accelerating the catalytic reaction rate. Furthermore, the Ru nanoclusters can efficiently cleave H₂ molecules, significantly accelerating the hydrogenation process of reaction intermediates and improving reaction efficiency. Meanwhile, there is a significant metal-support strong interaction between Ru nanoclusters and Nb2O5 support, which can effectively regulate the electronic structure of the catalyst surface, enhance the adsorption and activation ability of active sites for reactants, effectively suppress the occurrence of side reactions, achieve 100% high selectivity of methane product, and significantly improve the photothermal synergistic catalytic efficiency and recycling stability of the catalyst.
[0038] This invention discloses a method for preparing a catalyst for solar thermal-driven carbon dioxide hydrogenation to methane, characterized by comprising the following steps:
[0039] 1) Preparation of niobic acid precursor: Dissolve soluble niobium (Nb) raw material in ethanol, add an appropriate amount of water and stir evenly. Then, add concentrated ammonia (mass fraction 25%–28%) dropwise to the mixture while stirring continuously to form a suspension. Centrifuge to collect the solid precipitate. Dissolve polyvinylpyrrolidone (PVP-K30) in water to prepare an aqueous solution. Then, add the above solid precipitate to the PVP aqueous solution and stir thoroughly to form a suspension. Transfer the suspension to a polytetrafluoroethylene-lined high-pressure reactor, seal it, and react at 160–200 °C for 18–24 h. After the reaction, cool naturally to room temperature, centrifuge to collect the solid precipitate, and wash and dry it to obtain the niobic acid precursor.
[0040] 2) Preparation of nano-flower-like Nb2O5 support: The niobate precursor obtained in step 1) was ground thoroughly in a mortar, transferred to a porcelain boat, and calcined at a constant temperature of 400-600 °C for 2-4 h in an air atmosphere. Then it was cooled to room temperature and ground again to obtain nano-flower-like Nb2O5 support.
[0041] 3) Ru NCPreparation of Nb₂O₅ catalyst: A certain amount of Nb₂O₅ support was weighed and added to an aqueous solution containing ruthenium precursor, which was ultrasonically dispersed evenly. Photodeposition reaction was carried out under an inert protective atmosphere and light irradiation. After the reaction was completed, the solid product was collected by centrifugation and dried under vacuum to obtain Ru. NC / Nb2O5 catalyst.
[0042] The specific embodiments of the present invention are as follows:
[0043] Example 1
[0044] Ru NC Preparation of Nb2O5 catalyst:
[0045] 1) Preparation of niobic acid precursor: Weigh 200 mg of NbCl5 and dissolve it in 4 g of ethanol, then add 20 g of deionized water and stir thoroughly until homogeneous. Then, slowly add 4 mL of 25 wt% concentrated ammonia solution dropwise while stirring continuously for 1 h to form a homogeneous suspension. Collect the solid precipitate by centrifugation. Weigh 0.4 g of PVP (K30) and dissolve it in 40 mL of deionized water to prepare a PVP aqueous solution. Then, add the above solid precipitate to the PVP aqueous solution and stir continuously to form a homogeneous suspension. Transfer the resulting suspension to a polytetrafluoroethylene-lined hydrothermal reactor and react at 180 ℃ for 24 h. After the reaction, allow it to cool naturally to room temperature, collect the solid product by centrifugation, and obtain niobic acid precursor solid powder after washing and drying.
[0046] 2) Preparation of Nb2O5 support by calcination of precursor: The precursor solid powder prepared above was placed in a mortar and ground thoroughly, then transferred to a magnetic boat and calcined at 500 °C for 2 h in air atmosphere. After naturally cooling to room temperature, it was ground thoroughly again to obtain nanoflower-like Nb2O5 support.
[0047] 3) Loading Ru nanoclusters: 20 mg of the Nb₂O₅ support prepared above was ultrasonically dispersed in 20 mL of a 0.2 mmol / L RuCl₃ aqueous solution; under nitrogen protection, an optical power density of 100 mW·cm⁻¹ was used for the dispersion. -2 The mixture was irradiated with ultraviolet-visible light (320-780 nm) for 1 h. After the reaction was complete, the precipitate was collected by centrifugation, thoroughly washed with deionized water, and dried under vacuum at 60 °C for 12 h to obtain the target catalyst, denoted as Ru. NC / Nb2O5.
[0048] Example 2
[0049] The difference between this embodiment and Example 1 is that the concentration of the RuCl3 aqueous solution in step 3) is changed to 0.1 mmol / L, and the resulting catalyst is denoted as Ru.NC (1 wt.%) / Nb2O5.
[0050] Example 3
[0051] The difference between this embodiment and Example 1 is that the concentration of the RuCl3 aqueous solution in step 3) is changed to 0.3 mmol / L, and the resulting catalyst is denoted as Ru. NC (3 wt.%) / Nb2O5.
[0052] Example 4
[0053] The difference between this embodiment and Example 1 is that the concentration of the RuCl3 aqueous solution in step 3) is changed to 0.4 mmol / L, and the resulting catalyst is denoted as Ru. NC (4 wt.%) / Nb2O5.
[0054] Comparative Example 1
[0055] The difference between this comparative example and Example 1 is that step 3 is omitted, and the resulting catalyst is denoted as Nb2O5.
[0056] Comparative Example 2
[0057] The difference between this comparative example and Example 1 lies in the change of the Ru loading method in step 3). Specifically, 20 mg of Nb₂O₅ support was weighed and dispersed in 20 mL of a 0.2 mmol / L RuCl₃ aqueous solution. Then, 0.2 g of L-ascorbic acid was added to the dispersion, and the mixture was stirred continuously until completely dissolved. The system was then heated to 80 °C and stirred at this temperature for 2 h. After the reaction, the solid precipitate was collected by centrifugation, washed with deionized water, and vacuum dried at 60 °C for 12 h. The resulting comparative catalyst was denoted as Ru. NP / Nb2O5.
[0058] Comparative Example 3
[0059] The difference between this comparative example and Example 1 is that step 3) is changed to the following operation: 20 mg of Nb₂O₅ is weighed and dispersed in 20 mL of 0.2 mmol / L RuCl₃ aqueous solution, and stirred for 2 h under light-protected conditions for adsorption. The precipitate is collected by centrifugation, washed with deionized water, and then vacuum dried at 60 °C for 12 h. The resulting comparative catalyst is denoted as Ru. SA / Nb2O5.
[0060] Comparative Example 4
[0061] The difference between this comparative example and Example 1 is that step 3) is changed to the following operation: 20 mg of Nb2O5 is weighed and dispersed in 20 mL of 0.2 mmol / L RuCl3 aqueous solution, stirred and adsorbed for 2 h under light-protected conditions, then the precipitate is collected by centrifugation, washed with deionized water and dried under vacuum at 60 °C. Finally, the dried solid is placed in a magnetic boat and calcined at 350 °C for 2 h in air atmosphere. The resulting comparative catalyst is denoted as RuO2 / Nb2O5.
[0062] The catalysts prepared in Example 1 and Comparative Examples 1-4 were analyzed. For example... Figure 1 As shown, the XRD patterns of all prepared catalysts exhibited similar diffraction peaks, all corresponding to the diffraction peaks of pseudo-hexagonal Nb₂O₅ (PDF#28-0317), with the characteristic peaks at 2θ ≈ 22.6° and 28.6° corresponding to the (001) and (100) crystal planes of pseudo-hexagonal Nb₂O₅. No diffraction peaks related to Ru-containing species were observed, which can be attributed to the low Ru content and high dispersion of Ru on the catalyst surface.
[0063] Figure 2 Ru prepared in Example 1 NC SEM image of the / Nb2O5 catalyst. As shown in the figure, the catalyst exhibits a three-dimensional flower-like spherical structure formed by the stacking and assembly of nanosheets. The particle size of the microspheres is about 1-2 μm. The sample has uniform size, good dispersion, and regular morphology.
[0064] Figure 3 The images show transmission electron microscopy (TEM), high-resolution transmission electron microscopy (HRTEM), high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM), and corresponding elemental mapping images of the catalyst in Example 1. Figure 3 This further proves that the Nb2O5 carrier is a three-dimensional flower-like microstructure formed by the assembly of nanosheets. Figure 3 b is a magnified TEM image, which clearly shows that Ru nanoclusters with a particle size concentrated in the range of 0.9–1.4 nm are uniformly attached to the surface of Nb₂O₅ nanosheets without obvious agglomeration. Figure 3 Clear lattice fringes can be observed in the HRTEM image shown in c, corresponding to the (001) characteristic crystal plane of Nb2O5. Figure 3 The elemental mapping results of dg show that Ru is highly uniformly distributed on the surface of Nb2O5 without obvious agglomeration, further confirming that Ru species are uniformly loaded in the form of ultra-small nanoclusters without large Ru nanoparticles.
[0065] Figure 4 a and Figure 4b shows the N2 isothermal adsorption-desorption curves and corresponding pore size distributions of the catalysts prepared in Example 1 and Comparative Example 1, respectively. The test results indicate that both catalysts possess large specific surface areas and distinct pore structures. Specifically, the specific surface area of the catalyst in Example 1 is 77.69 m². 2 ·g -1 The value was significantly higher than that of the catalyst in Comparative Example 1, which was 56.92 m. 2 ·g -1 This result can be attributed to the fact that the catalyst surface of Example 1 has a greater abundance of oxygen vacancies, which effectively increases the material's pore capacity and adsorption contact area, thus giving the material superior gas adsorption performance.
[0066] Figure 5 a shows the XPS full spectrum of the catalysts in Example 1 and Comparative Example 1. The spectral results show that Ru, Nb, and O can be detected in the catalyst of Example 1, while only Nb and O are observed in the catalyst of Comparative Example 1, proving that Ru species were successfully loaded onto the surface of the Nb2O5 support. Figure 5 bd represents the Nb 3 of the catalysts prepared in Example 1 and Comparative Example 1, respectively. d O 1 s and Ru3 p A detailed XPS spectrum. For example... Figure 5 As can be seen from b, after loading Ru nanoclusters, Nb 3 d With O 1 s The characteristic binding energy shifts towards lower energies, indicating that the introduction of Ru species effectively modulates the surface electronic structure of the Nb₂O₅ support, and that electrons are transferred from Ru nanoclusters to the Nb₂O₅ support, thus establishing a good metal-support interaction. Figure 5 As can be seen from c, the relative content of oxygen adsorbed on the surface of the catalyst in Example 1 is significantly higher than that of the catalyst in Comparative Example 1, indicating that there is a higher concentration of oxygen vacancies on its surface, which can provide more active sites for CO2 adsorption and activation. Figure 5 d of Ru 3 p Fine spectroscopy further confirmed that Ru in the catalyst of Example 1 was in a metallic state (Ru 0 ) and oxidation state (Ru δ+ The coexistence of these substances and the synergistic effect of mixed-valence Ru active sites can effectively optimize the catalytic reaction pathway and improve catalytic performance.
[0067] Specific applications of this invention are as follows:
[0068] Application Example 1
[0069] The various catalysts prepared in this invention are applied to the batch photothermal catalytic CO2 hydrogenation reaction. The experimental procedures are as follows:
[0070] 1) Weigh 5 mg of catalyst, evenly disperse it on quartz wool into circles with a diameter of about 1 cm, place it in a quartz reactor with a volume of 170 mL, seal it, and introduce a CO2 / H2 (1:3) mixture into the reactor for 30 minutes to stabilize the pressure at 0.10 MPa.
[0071] 2) Xe lamps were used as the light source to provide simulated sunlight with wavelengths mainly in the range of 320-1100 nm, and the maximum light power density irradiating the catalyst surface was 2.5 W·cm⁻¹. -2 The catalytic CO2 hydrogenation reduction reaction was carried out, and samples were taken every 1 hour. The products were analyzed using gas chromatography.
[0072] Figure 6 The results show the performance of the catalysts prepared in Examples 1-4 and Comparative Example 1 in the photothermal catalytic CO2 hydrogenation reaction. The results indicate that the catalyst in Comparative Example 1 has almost no CO2 hydrogenation reduction ability, while Example 1 (theoretical Ru loading of 2 wt.%) exhibits the best catalytic activity, with a CH4 formation rate reaching 114.74 mmol·g⁻¹. -1 ·h -1 The selectivity was 100%. As the Ru loading gradually increased, the CH4 formation rate of the catalyst showed a volcano-like trend of first increasing and then decreasing.
[0073] Figure 7 The figures show the catalytic performance of the catalysts prepared in Example 1 and Comparative Examples 2-4 in the photothermal catalytic CO2 hydrogenation reaction and the temperature of the catalyst surface during the reaction. The results show that the catalyst in Example 1 exhibits the highest CH4 formation rate (114.74 mmol·g⁻¹). -1 ·h -1 The catalysts in Examples 2-4 also exhibited high surface temperatures and significant catalytic activity, but their catalytic performance was significantly lower than that of the catalyst in Example 1. Their surface temperatures were 350.0 °C, 322.8 °C, and 321.7 °C, respectively, with corresponding CH4 formation rates of 55.86 mmol·g⁻¹. -1 ·h -1 38.67 mmol·g -1 ·h -1 and 7.47 mmol·g -1 ·h -1 All catalysts exhibited 100% CH4 selectivity.
[0074] Application Example 2
[0075] The catalyst prepared in Example 1 was applied to a batch photothermal catalytic CO2 hydrogenation reaction. The experimental procedure is as follows:
[0076] 1) Weigh 5 mg of catalyst, evenly disperse it on quartz wool into circles with a diameter of about 1 cm, place it in a quartz reactor with a volume of 170 mL, seal it, and introduce a mixture of CO2 / H2 / N2 (1:3:6 or 1:3:36) of different concentrations into the reactor for 30 minutes, and stabilize the pressure at 0.10 MPa.
[0077] 2) Xe lamps were used as the light source to provide simulated sunlight with wavelengths mainly in the range of 320-1100 nm, and the maximum light power density irradiating the catalyst surface was 2.5 W·cm⁻¹. -2 The catalytic CO2 hydrogenation reduction reaction was carried out, and samples were taken every 1 hour. The products were analyzed using gas chromatography.
[0078] Figure 8 The catalytic performance of the catalyst prepared in Example 1 is shown in reaction systems with different CO2 concentrations. Under CO2 concentrations of 10% and 2.5%, the CH4 formation rate reached 76.57 mmol·g⁻¹. -1 ·h -1 and 26.90 mmol·g -1 ·h -1 The catalyst maintains a considerable CH4 generation rate in the low CO2 concentration range (2.5%–10%), demonstrating excellent adaptability to low-concentration CO2 and proving its great application potential in practical application scenarios such as low-concentration CO2 capture and conversion and low-altitude carbon resource utilization.
[0079] Application Example 3
[0080] The catalyst prepared in Example 1 was applied to a flow-type photothermal catalytic CO2 hydrogenation reaction. The experimental procedure is as follows:
[0081] 1) Weigh 5 mg of catalyst, evenly disperse it on quartz wool into circles with a diameter of about 1 cm, place it in a quartz reactor with a volume of 50 mL, seal it, and continuously introduce CO2 / H2 (1:3) mixed gas into the reactor at a gas flow rate of 10 mL / min and a pressure of 0.10 MPa.
[0082] 2) Xe lamps were used as the light source to provide simulated sunlight with wavelengths mainly in the range of 320-1100 nm, and the maximum light power density irradiating the catalyst surface was 2.5 W·cm⁻¹. -2 The catalytic CO2 hydrogenation reduction reaction was carried out, and samples were taken every 1 hour. The products were analyzed using gas chromatography.
[0083] Figure 9The results show the CH4 formation rate and stability of the catalyst prepared in Example 1 during a continuous flow reaction. The results indicate that the average CH4 formation rate of this catalyst reaches 578 mmol·g during a long-term flow reaction. -1 ·h -1 Furthermore, the selectivity for CH4 products was 100% throughout the entire reaction process. Under continuous reaction conditions lasting up to 80 hours, the catalytic activity of this catalyst did not show significant decline, maintaining a stable reaction efficiency throughout, fully demonstrating the effectiveness of this Ru catalyst. NC / Nb2O5 catalysts exhibit excellent structural stability and catalytic durability in the photothermal catalytic CO2 hydrogenation to methane reaction, meeting the application requirements for long-term continuous catalytic reactions.
[0084] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to specific implementations. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.
Claims
1. A catalyst for solar thermal-driven carbon dioxide hydrogenation to methane, characterized in that, The catalyst is a ruthenium-based supported catalyst, which is composed of ruthenium nanoclusters and niobium pentoxide support; the niobium pentoxide support is a flower-like hierarchical structure formed by assembling nanosheets, and the ruthenium nanoclusters are uniformly loaded on the surface of the nanosheets of the niobium pentoxide support.
2. The catalyst for solar thermal-driven carbon dioxide hydrogenation to methane according to claim 1, characterized in that, The ruthenium nanoclusters have a particle size distribution of 0.9–1.4 nm.
3. The catalyst for solar thermal-driven carbon dioxide hydrogenation to methane according to claim 1, characterized in that, The method for preparing the catalyst includes the following steps: 1) Preparation of niobic acid precursor: Soluble niobium-containing raw material is dissolved in a mixture of ethanol and water, stirred evenly, and concentrated ammonia is added dropwise to form a suspension. The solid precipitate is collected by centrifugation. The solid precipitate is dispersed in an aqueous solution of polyvinylpyrrolidone, stirred evenly, and subjected to a hydrothermal reaction. After the reaction is completed, the mixture is cooled, centrifuged, washed, and dried to obtain the niobic acid precursor. 2) Carrier preparation: The niobate precursor was ground, calcined in air, cooled, and ground again to obtain a nano-flower-like niobium pentoxide carrier; 3) Catalyst preparation: The niobium pentoxide support was dispersed in an aqueous solution containing ruthenium precursor and ultrasonically homogenized. Photodeposition reaction was carried out under an inert protective atmosphere and light irradiation. After the reaction was completed, the catalyst was centrifuged and vacuum dried to obtain the target catalyst.
4. The catalyst for solar thermal-driven carbon dioxide hydrogenation to methane according to claim 3, characterized in that, In step 1), the hydrothermal reaction temperature is 160–200 °C, and the hydrothermal reaction time is 18–24 h; the mass fraction of the concentrated ammonia solution is 25%–28%.
5. The catalyst for solar thermal-driven carbon dioxide hydrogenation to methane according to claim 3, characterized in that, In step 1), the mass ratio of Nb, ethanol, and water is 0.2–1:20:100, the mass ratio of concentrated ammonia to water is 3–5:20, and the mass ratio of polyvinylpyrrolidone to water is 0.5–2:
100.
6. The catalyst for solar thermal-driven carbon dioxide hydrogenation to methane according to claim 3, characterized in that, In step 2), the calcination temperature is 400–600 °C and the calcination time is 2–4 h.
7. The catalyst for solar thermal-driven carbon dioxide hydrogenation to methane according to claim 3, characterized in that, In step 3), the mass ratio of niobium pentoxide, Ru, and water is 0.02:0.0001 to 0.0016:
20.
8. The application of the catalyst according to any one of claims 1-7 in a solar thermal-driven reaction of carbon dioxide hydrogenation to methane.
9. The application according to claim 8, characterized in that, The carbon dioxide hydrogenation to methane reaction is a gas-solid photothermal catalytic reaction. The reaction system is either a batch reaction system or a continuous flow reaction system. The reaction process uses solar energy as the sole energy source, requiring no additional heating, and the methane selectivity of the reaction product can reach 100%.